PENGARUH ETIKA KERJA ISLAMI DAN KEPRIBADIAN TERHADAP KREATIVITAS KARYAWAN - Putri Rahayu Wulan Sari; Keumala Hayati; Rr. Erlina (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the effect of Islamic work ethics and personality on creativity. Personality is seen from five factors: extraversion, agreeableness, conscientiousness, neuroticism, and openness to experience. Data collection was carried out using a questionnaire with a total sample of 103 Syari'ah Bank employees in Bandar Lampung. The results showed that Islamic work ethics influenced the creativity of Islamic banking employees. The results also found that of the five personalities (extraversion, agreeableness, conscientiousness, neuroticism, openness to experience), only agreeableness and openness to experience affected employee creativity.